BacA: a possible regulator that contributes to the biofilm formation of Pseudomonas aeruginosa - Wallart, Lisa; Ben Mlouka, Mohamed Amine; Saffiedine, Brahim; Coquet, Laurent; Le, Hung; Hardouin, Julie; Jouenne, Thierry; Phan, Gilles; Kiefer-Meyer, Marie-Christine; Girard, Eric; Broutin, Isabelle; Cosette, Pascal (Frontiers in Microbiology, 2024)
Previously, we pointed out in P. aeruginosa PAO1 biofilm cells the accumulation of a hypothetical protein named PA3731 and showed that the deletion of the corresponding gene impacted its biofilm formation capacity. PA3731 belongs to a cluster of 4 genes (pa3732 to pa3729) that we named bac for "Biofilm Associated Cluster". The present study focuses on the PA14_16140 protein, i.e., the PA3732 (BacA) homolog in the PA14 strain. The role of BacA in rhamnolipid secretion, biofilm formation and virulence, was confirmed by phenotypic experiments with a bacA mutant. Additional investigations allow to advance that the bac system involves in fact 6 genes organized in operon, i.e., bacA to bacF. At a molecular level, quantitative proteomic studies revealed an accumulation of the BAC cognate partners by the bacA sessile mutant, suggesting a negative control of BacA towards the bac operon. Finally, a first crystallographic structure of BacA was obtained revealing a structure homologous to chaperones or/and regulatory proteins.